2011
DOI: 10.1002/jhm.869
|View full text |Cite
|
Sign up to set email alerts
|

Use of pharmacodynamic principles to inform β‐lactam dosing: “S” does not always mean success

Abstract: Dose optimization is one of the key strategies for enhancing antimicrobial stewardship. There have been tremendous strides in our understanding of antibiotic exposure-response relationships over the past 25 years. For many antibiotics, the ''pharmacodynamic'' or the exposure variable associated with outcome has been identified. With advances in mathematical modeling, it is possible to apply our understanding of antimicrobial pharmacodynamics (PD) into clinical practice and design empirical regimens that have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The PD target most correlated to maximal bactericidal activity for beta-lactams is the time in which free drug concentrations remain above the MIC (TϾMIC) (17). The total, rather than free, drug concentration was used in this study due to low protein binding of ampicillin (ϳ10%) reported in neonates (18).…”
Section: Methodsmentioning
confidence: 99%
“…The PD target most correlated to maximal bactericidal activity for beta-lactams is the time in which free drug concentrations remain above the MIC (TϾMIC) (17). The total, rather than free, drug concentration was used in this study due to low protein binding of ampicillin (ϳ10%) reported in neonates (18).…”
Section: Methodsmentioning
confidence: 99%
“…Adequate antibiotic concentrations at the site of infection are critical to ensure the highest probability of favorable clinical and microbiological responses (16,17). Significant advances have been made in identifying the exposure target associated with the maximal response for many classes of antibiotics (2,7,9,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Significant advances have been made in identifying the exposure target associated with the maximal response for many classes of antibiotics (2,7,9,16,17). For carbapenem antibiotics such as ertapenem, studies have demonstrated that the microbiological response is optimized when concentrations exceed the MIC for 30 to 40% of the dosing interval (7,9,22,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations are derived from animal experiments; clinical investigations underscore the fact that in sepsis patients, an fT>MIC of 100% elicits a more effective anti-infective effect, and is thus relevant for outcome [190,[201][202][203]. Especially on the basis of striving to achieve adequate tissue concentrations even in deep-lying compartments (pneumonia; bone infections; infections of the central nervous system, CNS)-frequently in the context of disturbed microcirculation in sepsis patients [204][205][206] and also wishing to avoid development of resistance [207,208]-many experts recommend aiming for a concentration of β-lactam antibiotics in the primary compartment (serum/plasma) that exceeds the MIC by 4-times (up to 6-times) for 60-100% of the dosing interval [209]. In addition to individual dosing of antibiotics, the current DGI guideline [124] names therapeutic drug monitoring (TDM) as a possibility for treatment management and reduction of undesirable side effects of antibiotics.…”
Section: Pharmacokinetic Conceptsmentioning
confidence: 99%